Canada. Significant achievements 2022 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
The Canadian Delegation carried out activities in collaboration with the USDA and a network of national agricultural research bodies (PROCINORTE), to support ASF diagnostic training and research collaborations across the Caribbean with a first project in Trinidad and Tobago. On technical cooperation, the delegation pursued multiple development project bids, provided technical cooperation services on food system transformation, and genomic-based solutions to climate-smart agriculture, while developing new partnerships with Canadian institutions. The Delegation also co-hosted several hybrid and virtual regional and hemispheric workshops including a series of 5 webinars on Sustainable Livestock in the Americas, funded by IFAD. The Delegation also took part in multiple Canadian and international agriculture, food security and sustainability conferences, including numerous speaking and moderating opportunities, providing guidance, thought leadership and development solutions to advance agricultural and rural development in the Americas.